The Role of the Thymus in the Control of Autoimmunity - Heath, Victoria L.; Saoudi, Abdelhadi; Seddon, Benedict P.; Moore, Nel C.; Fowell, Deborah J.; Mason, Don W. (Journal of autoimmunity, 1996)
Self tolerance among T cells is believed to be maintained by two principal mechanisms: clonal deletion for self antigens expressed in the thymus and T cell anergy or T cell indifference for those whose expression is solely extra-thymic. These mechanisms are passive in that they depend on autoreactive T cells being either eliminated during their maturation or rendered intrinsically non-responsive after they have matured. The data presented in this paper indicate that this scheme requires modification. First, it is evident that self antigens that are commonly regarded as being tissue-specific may also be expressed in the thymus where they influence the developing T cell repertoire. Second, it appears that there is some T cell-mediated regulatory mechanism that actively prevents potentially autoreactive T cells from expressing their disease-inducing potential. Our data indicate that this regulatory mechanism is established intrathymically and is an innate property of the naive T cell repertoire. The mechanism is discussed in terms of what is currently known of the ways that an individual T cell responds when interacting with agonist and antagonist peptides and possible therapeutic implications are considered.